ANALISIS VIDEO PEMBELAJARAN DARING DALAM PERMASALAHAN SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Nurlayli Nurlayli; Djatmiko Hidajat; Ethina Primasari (Universitas Halu Oleo, 2021)
This research is a descriptive qualitative type of research which aims to determine mathematics learning achievement in the online learning by using video material process in three-variable linear equation system problems which is carried out due to the presence of Coronavirus-Diseases (COVID 19) in class X at Senior High School of Veteran 1 Sukoharjo so that it can be seen that student achievement is decreased or increased. The subject of this study were the result of tests and interviews. The data collection strategy was done by using the test method. Data validation by triangulation namely by comparing the results of test data.. Qualitative data anlysisi techniques which include the stages of data reduction. Data presentation, and verification and drawing coclusions. Based on the result of this study, it can be seen that student achievemenet in the three variable linear equation system material increases with online learning using the material video method. So, it can be said that this method is effective to implement.